Responsible innovation in business: a critical reflection on deliberative engagement as a central governance mechanism. Issue 1 (2nd January 2019) - Brand, Teunis; Blok, Vincent
ABSTRACT: One of the main contentions of the framework for Responsible Innovation (RI) is that social and ethical aspects have to be addressed by deliberative engagement with stakeholders and the wider public throughout the innovation process. The aim of this article is to reflect on the question to what extent is deliberative engagement suitable for conducting RI in business. We discuss several tensions that arise when this framework is applied in the business context. Further, we analyse the place of deliberative engagement in several theories of business ethics. We conclude that there remains a tension between the ideal of RI and the way in which the competitive market operates. Hence, RI scholars should reflect more critically on changes that are required in the market in order to make RI possible, modify the ideal of deliberative engagement for RI in business, or attempt to strike a balance between these two responses.